Síntese de azinas assistida por micro-ondas e avaliação da atividade anticolinesterásica - (:unkn) unknown (Universidade Estadual de Goiás, 2015)
The azines that are compounds formed from hydrazones and exhibit several biological activities, among them anticholinesterase activity, used in the treatment of Alzheimer's disease. In Alzheimer's disease (AD), a neurodegenerative multifactorial and complex disease primarily affecting the elderly population over 65 years old are observed cognitive and functional deficits. Evidence has shown that these deficits relate to the degeneration of the cholinergic system, mainly due to the reduction of plasma levels of acetylcholine. AD patients show improvement of cognitive, behavioral and functional symptoms related to hypocholinergic dementias, when treated with acetylcholinesterase (AChE) inhibitors. These inhibitors increase levels of acetylcholine present in the synapses between cholinergic neurons. The main class of inhibitor medicines (AChE) are tacrine, donepezil, galantamine and rivastigmine, justifying the search for more potent and with less toxicity AChE inhibitors. Studies suggest structural similarities between the donepezil and some azines. Thus the aim of this study was to synthesize using microwave irradiation, identify the structure of the synthesized compounds and perform anticholinesterase test a number of azines, similar to donepezil. These azines were synthesized and tested, verifying that the azines 20 and 29 synthesized using a modified Ellman's test for chromatographic plates inhibited acetylcholinesterase, but confirm the test making false positive test that has not confirmed the inhibition acetylcholinesterase by these compounds, the compounds 16, 17, 18, 22, 23,25, 26, 27 and 30 no enzyme inhibition but chemical reaction between the thiocholine and compounds, and compounds 19, 21, 24, 28 and 31 showed no activity nor reacted with thiocholine. Concluding that the irradiation Microwave technique is quite effective in organic synthesis, reduced the time, the cost of the reaction and the amount of solvent released into the environment. Because of azines present biological activities described in the literature, such as antitumor, anti-coagulant, among other platelet is suggested to make other tests with azines synthesized to evaluate if present other biological activities.
Keywords: Síntese; Micro-ondas; Atividade Anticolinesterásica; Hidrazona, Azina; Synthesis; Microwave; acetylcholinesterase activity; Hydrazone; Azine; CIENCIAS EXATAS E DA TERRA::QUIMICA; QUIMICA::QUIMICA ORGANICA